Pieces Analysis to Improve Performance Cash Sales System: A Case Study on The Darmo Deli Supermarket - anisa fitri syabania (TIJAB (The International Journal of Applied Business), 2022)
Darmo Deli Supermarket is a growing retail company. Cash sales is the  main source income for that company. In order  to  improve  its  performance,  it  is  deemed  necessary  to  conduct  an  analysis  of  the  cash  sales system  at  the Darmo  Deli  supermarket.  A  qualitative  approach  with  observation, interviews, and documentation was  used  to  obtain  information  about  the  cash sales  flow  and  system  that  had  been implemented.  PIECES analysis has 6 aspects, performance, information, economic, control, efficiency and service. The results of the study show that the Darmo Deli Supermarket cash sales accounting information system has no warehouse section. Based on  PIECES analysis, the  control aspect of the cash sales system needs to be improved. So that, the fraudulent sales data reporting can be avoided, velocity and accuracy of financial reports  in Darmo Deli Supermarket cash sales system can enhanced.